Land as a Site of Remembrance: An Ethnographic study in Barkly East - Nortje, Karen (My University, 2007)
This thesis is an examination of the ways in which people in Barkly East, a small town in the Eastern Cape, attribute feelings of belonging to the land they own and work. In a country such as South Africa, where the contestation of land is prominent and so integral to the political and social discourse, questions related to the idea of belonging are necessary and important. Significant questions addressed by this thesis are: Who belongs and why do they feel they belong? More importantly, the question of who does not belong, is addressed. In Barkly East a tug of war exists between groups and individuals who want matters to remain constant and those who need the status quo to change. What stands out, moreover, in this community, is its duality on many levels of society, which is played out both consciously and unconsciously. This duality is also manifested through social, racial and economic relations, and is supported by an unequal access to land. This thesis identifies three main elements which contribute to the creation of narratives of belonging in Barkly East. Firstly, history and the perception of history create strong links between personal and communal identity, which in turn reinforces and legitimises claims of belonging. Secondly, hierarchy in terms of gender and race plays an important part in this narration, as some residents are more empowered in this process due to either their gender or race. And three, the connection to the land that people appear to have, plays a definitive role in narratives of belonging. Those who feel they have a heritage in this place also feel a connection to the land. For this reason, land for these people embody, not only the physical space of somewhere to belong to, but becomes an integral ingredient to the act of belonging and even identity formation.
Student Number: 9606978D Masters in Social Anthropology School of Social Sciences
Keywords: Land Rights; Memory; Heritage; Beloning; Eastern Cape; Levels of Society; Social, racial and economic relations; History perception; Communal Identity; Connection